ADAPTATIONS IN THE VASCULAR SURGERY DEPARTMENT OF THE CHULN DURING THE COVID-19 PANDEMIC AND IMPACT ON OVERALL ACTIVITY - Duarte, António (2020)
With the onset of the SARS-CoV-2 pandemic in early 2020, health services and personnel adapted their resources to mitigate and control the outbreak. These needs inevitably led to adaptations in most medical and surgical departments, including in our Vascular Surgery department. As we are facing a second outbreak of this pandemic, with unpredictable outcomes and repercussions in health services, it is crucial to learn from previous experiences and share strategies to perform the best care to our patients, despite the restrictions that have been imposed. Through this paper, we review the adaptations in Centro Hospitalar Universitário Lisboa Norte and particularly in our department to overcome the pandemic. We also assess the impact of these changes in our activity and compare with the experience of other fellow surgeons. With an upcoming second outbreak, it is crucial to learn from this and other departments’ experiences to overcome a potential health crisis.